Skin cancer and the dangers of UV rays (Research, Society and Development, 2022)
Skin cancer happens when skin cells grow and multiply in an uncontrolled and disordered way. Normally, new skin cells form when the cells age and die or when they are damaged. When this process does not work as it should, cells (some of which may be abnormal cells) grow rapidly. Aiming to review in the literature the dangers of ultraviolet rays for skin cancer. This is an integrative literature review carried out through the SciELO, LILACS, BDENF and MEDLINE databases, through the following DeCS: “Neoplasms”, “Skin Neoplasms” and “Ultraviolet Rays”. As inclusion criteria: articles available online, in full, in Portuguese, English and Spanish, that addressed the topic in the last ten years. As exclusion criteria: articles that did not cover the topic and repeated studies between databases. The main cause of skin cancer is excessive exposure to sunlight, especially when it results in sunburn and blisters. The sun's ultraviolet (UV) rays damage the skin's DNA, causing abnormal cells to form. These abnormal cells divide rapidly in a disorganized way, forming a mass of cancer cells. The skin is the largest organ in your body, so it needs as much attention as any other health problem. What may seem like an innocent cosmetic imperfection may not be. Performing regular skin checks is important for everyone and is especially important if the person already has a family history of a person at increased risk of skin cancer.